Determinants of Household Perceptions and Acceptance of Sago as a Local Staple Substitute - Natal Basuki; Nursamsi Nursamsi; Haris Mahmud; Suhardi Suhardi (SCIENTIA: Journal of Multi Disciplinary Science, 2026)
Research on local food systems has often overlooked the comprehensive dynamics of household perceptions, particularly in archipelagic regions characterized by high levels of food vulnerability. This study aimed to examine the determinants of household perceptions and acceptance of sago (Metroxylon sagu) as a local staple food substitute in Tidore, Indonesia. A quantitative approach was employed through a survey of 88 households selected using proportional random sampling from a population of 728 households. Data were collected using a structured Likert-scale questionnaire and analysed using descriptive statistics, perception index analysis, and multiple linear regression. The findings revealed that household perceptions of sago were generally high, as reflected by the accessibility and availability index (76.74), nutrition and health awareness index (87.84), social acceptance index (88.18), and economic value and food security index (85.97). Multiple regression analysis indicated that age (B = 2.31, p = 0.021), education (B = 3.59, p < 0.001), and household size (B = 5.19, p < 0.001) had positive and statistically significant effects on household perceptions of sago. In contrast, household income showed no significant effect (B = −1.97, p = 0.11), while the model explained 54.7% of the variance in household perceptions (R² = 0.547). These findings provide empirical evidence that sago represents a strategic local food resource for strengthening food security in archipelagic regions. The study highlights the need for local governments to formulate integrated food diversification policies and promote value-added processing of sago-based products to reduce dependence on imported staple foods.